A case report and systematic literature review: insulin-induced type III hypersensitivity reaction - Meredith, Rebecca R.; Patel, Pooja; Huang, Polly; Onyenekwu, Chinelo Pamela; Rai, Herleen; Tversky, Jody; Alvarez-Arango, Santiago (Frontiers in Allergy, 2024)
Insulin-induced type III hypersensitivity reactions (HSRs) are exceedingly rare and pose complex diagnostic and management challenges. We describe a case of a 43-year-old woman with type 1 diabetes mellitus (DM), severe insulin resistance, and subcutaneous nodules at injection sites, accompanied by elevated anti-insulin IgG autoantibodies. Treatment involved therapeutic plasma exchange (TPE) and intravenous immunoglobulin (IVIg) as bridge therapy, followed by long-term immunosuppression, which reduced autoantibody levels and improved insulin tolerance. Given the limited treatment guidelines, we conducted a comprehensive literature review, identifying 16 similar cases. Most patients were females with a median age of 36.5 years; 63% had type 1 DM, and 44% had concurrent insulin resistance (56% with elevated autoantibodies). Treatment approaches varied, with glucocorticoids used in 67% of cases. Patients with type 1 DM were less responsive to steroids than those with type 2 DM, and had a more severe course. Of those patients with severe disease necessitating immunosuppression, 66% had poor responses or experienced relapses. The underlying mechanism of insulin-induced type III HSRs remains poorly understood. Immunosuppressive therapy reduces anti-insulin IgG autoantibodies, leading to short-term clinical improvement and improved insulin resistance, emphasizing their crucial role in the condition. However, the long-term efficacy of immunosuppression remains uncertain and necessitates continuous evaluation and further research.